NONLINEAR CONTRACTIONS AND FIXED POINTS IN COMPLETE DISLOCATED AND b-DISLOCATED METRIC SPACES - Hoxha, Elida; Zoto, Kastriot; Sumati Kumari, Panda (Matematichki Bilten, 2014)
In this paper, we continue the study of complete dislocated and \(b\)-dislocated metric spaces and established some common fixed point theorems for one and two mappings. Our results generalizes and extend some existing results in the literature in a class effectively larger such as \(b\)-dislocated metric spaces, where the self distance for a point may not be equal to zero.